Processos de resistência de mulheres camponesas: olhares pela perspectiva decolonial - Borges Kempf, Renata (2019)
This article discusses the dynamics of resistance of peasant women, observing how they, in specific contexts, construct collective actions that produce changes in the relations of power and oppression. The analysis is a case study in a family agroindustry in Pranchita-PR, oriented by the decolonial perspective. We observe that women farmers experience situations that differentiate them from urban women and also from peasants (men). As part of both categories (woman and peasant) they suffer doubly the effects of modernity and colonization. In this way the object of the article lays at the intersection of both categories - peasant woman.